Zoogeographical division of Vietnam based on the oribatid mite (Acari: Oribatida) fauna - Manh, Vu Quang (Academia Journal of Biology, 2016)
Soil oribatid mites (Acari: Oribatida) had been collected throughout Vietnam, including 50 sites located in 27 provinces, and from all of the 8 natural geographical regions. Up to December 2013, the oribatid fauna of Vietnam is represented by 320 species (including four subspecies) belonging to 163 genera, 64 families (including two subfamilies), and 30 superfamilies. 34.68% of the total number is probably endemic species. 155 oribatid species, representing 48.44% of the total oribatid fauna, were recorded for the first time for the fauna of Vietnam. The oribatid fauna of Vietnam occupies 3.09% (320 vs. 10,342 species), 13.05% (163 vs. 1,249 genera), and 38.0% (62 vs. 163 families) of the World oribatid fauna. Based on the analysis of the oribatid mite fauna, from North to South the zoogeographical division of Vietnam can be divided into six sub-divisions, as follows: (1) Region between Northwest and Northeast (North Vietnam), (2) Region of the Red River Delta (North Vietnam), (3) Region of the Red River Delta: National Park Cat Ba Island (North Vietnam), (4) Region of North Central: National Park Ben En (North Central Vietnam), (5) Region between the Uplands of the Red River Delta and the National Park Phong Nha - Ke Bang (North Vietnam and Central North Vietnam), and (6) Region of Southern (the Mekong River Delta): the National Parks of Bu Gia and of Cat Tien (South Vietnam).